The influence of lifestyle on airborne particle surface area doses received by different Western populations. (January 2018) - Pacitto, A.; Stabile, L.; Moreno, T.; Kumar, P.; Wierzbicka, A.; Morawska, L.; Buonanno, G.
Abstract: In the present study, the daily dose in terms of particle surface area received by citizens living in five cities in Western countries, characterized by different lifestyle, culture, climate and built-up environment, was evaluated and compared. For this purpose, the exposure to sub-micron particle concentration levels of the population living in Barcelona (Spain), Cassino (Italy), Guilford (United Kingdom), Lund (Sweden), and Brisbane (Australia) was measured through a direct exposure assessment approach. In particular, measurements of the exposure at a personal scale were performed by volunteers (15 per each population) that used a personal particle counter for different days in order to obtain exposure data in microenvironments/activities they resided/performed. Non-smoking volunteers performing non-industrial jobs were considered in the study. Particle concentration data allowed obtaining the exposure of the population living in each city. Such data were combined in a Monte Carlo method with the time activity pattern data characteristics of each population and inhalation rate to obtain the most probable daily dose in term of particle surface area as a function of the population gender, age, and nationality. The highest daily dose was estimated for citizens living in Cassino and Guilford (>1000 mm 2 ), whereas the lowest value was recognized for Lund citizens (around 100 mm 2 ). Indoor air quality, and in particular cooking and eating activities, was recognized as the main influencing factor in terms of exposure (and thus dose) of the population: then confirming that lifestyle (e.g. time spent in cooking activities) strongly affect the daily dose of the population. On the contrary, a minor or negligible contribution of the outdoor microenvironments was documented. Graphical abstract: Highlights: Evaluation of particle surface area daily dose received by different populations. Evaluation of the microenvironment and lifestyle effects on the daily dose. Measurement of the exposure to sub-micron particle concentrations at a personal level. Main contribution of the cooking activities on the overall daily dose. Abstract : The paper reports an evaluation of the airborne particle surface area doses received by different Western populations through a direct exposure assessment approach: such data may be used to calculate a-priori the human health effects by means of dose-risk models.